2018
DOI: 10.31788/rjc.2018.1144067
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF TOTAL PHENOLIC, FLAVONOID CONTENT, ANTIOXIDANT AND IN VITRO ANTILITHOGENESIS ACTIVITIES OF CHIVES LEAF (Allium schoenoprasum, L.)

Abstract: Natural resources and traditional medicines are important assets that need to be explored, researched, developed and optimized for their use. One of the natural resources that can be used as medicinal ingredients is chives (Allium schoenoprasum, L.), especially the leaf. Chives leaf contained a lot of phytochemical compounds which is potential as an antioxidant and antilithogenesis. The objective of this research is to evaluate the antioxidant and antilithogenesis activities of chives leaf extract. Antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…5 Recent reports revealed that phenolic components like flavonoids possibly form a complex with the calcium and potassium oxalates which could provide a potential cure for treating kidney stones. 6 Alkaloids, on the other hand, mimics the neuro transmitters' as agonists or antagonists in binding to the molecular receptors and their usage dates back to more than 5000 years as hallucinogens and psychotropic drugs. 7 Tannins enriched plant extracts are mostly used by the traditional practitioners as astringents, diuretics, to treat diarrhoea, to reduce ulceration of tumor tissues of the stomach and duodenum.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent reports revealed that phenolic components like flavonoids possibly form a complex with the calcium and potassium oxalates which could provide a potential cure for treating kidney stones. 6 Alkaloids, on the other hand, mimics the neuro transmitters' as agonists or antagonists in binding to the molecular receptors and their usage dates back to more than 5000 years as hallucinogens and psychotropic drugs. 7 Tannins enriched plant extracts are mostly used by the traditional practitioners as astringents, diuretics, to treat diarrhoea, to reduce ulceration of tumor tissues of the stomach and duodenum.…”
Section: Introductionmentioning
confidence: 99%
“…They have various biological activities such as antioxidant, anti-inflammatory, anti-allergic, anticarcinogenic, anti-mutagenic and modulatory effects on enzymatic activities. Flavonoids possess high antioxidant activities that can protect the body system against free radical and other diseases such as arteriosclerosis and diabetes 9,[26][27][28] .…”
Section: Total Flavonoid Contentmentioning
confidence: 99%
“…About 300 g of the fine powder coriander leaf was extracted with 96% ethanol by using maceration for 5 days at room temperature.The ethanol extract of coriander leaf (EECL) solution part was evaporated by using rotary evaporator to get the crude extract. 6,7 Preliminary Phytochemical Screening The crude extract of EELC was screening by using the standard protocol to know the presence of phytochemical compounds. 8…”
Section: Extract Preparationmentioning
confidence: 99%